Effect of Aloe vera (Aloe barbadensis Miller) on survivability, extent of proteolysis and ACE inhibition of potential probiotic cultures in fermented milk. (21st March 2014) - Basannavar, Santosh; Pothuraju, Ramesh; Sharma, Raj Kumar
Abstract BACKGROUND In the present investigation, the effect of Aloe vera gel powder on angiotensin‐converting enzyme (ACE) inhibitory activity, extent of proteolysis during fermentation and survival of Lactobacillus casei NCDC19 during storage of fermented milk was studied. RESULTS Among the different cultures screened for ACE inhibitory activity, Lactobacillus casei NCDC 19 exhibited the highest ACE inhibition (approx. 40%) as well as extent of proteolysis (0.37, Abs340). In the presence of Aloe vera (0.5% and 1% w/v) an increase in extent of proteolysis (0.460 ± 0.047 and 0.480 ± 0.027) and percent ACE inhibitory activity (44.32 ± 2.83 and 47.52 ± 1.83) was observed in comparison to control. Aloe vera powder addition also led to an increase in viable counts (>11 log cfu mL−1) of L. casei NCDC 19 in fermented milk during storage for 7 days and the counts were maintained in sufficiently higher numbers. CONCLUSION The study suggests Aloe vera to be a good functional ingredient which can be further explored for different health attributes. © 2014 Society of Chemical Industry